Synthesis and characterization of new unsaturated polyesters for composite applications / Norshahsillawati Azura Mohammad, Abdul Khalil Shawkataly and Issam Ahmed Mohammed - Mohammad, Norshahsillawati Azura; Shawkataly, Abdul Khalil; Mohammed, Issam Ahmed (2009)
Bis-(2-hydroxyethyl) fumarate (III) and Bis-(6-hydroxyhexyl) fumarate (IV) were synthesized from ethylene glycol and I, 6-hexanediol with fumaric acid in the presence of p-toluene sulfonic acid as catalyst. The chemical structures were confirmed by CHN analysis, FT-IR and IH-NMR spectroscopy. The new unsaturated polyesters were carried out by the condensation reaction between terepthaloyl chloride and monomer III and IV. The chemical structures of these polymers were confirmed by CHN analyses, FT-IR, JH-NMR, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). New oil palm empty fruit bunches reinforced polyester composite derived from the new unsaturated polyester resins containing bis-(2hydroxyethyl) fumarate and bis-(6-hydroxyhexyl) fumarate were prepared. The mechanical (tensile, flexural and impact properties) and physical properties (water absorption) of oil palm empty fruit bunches reinforced polyester composite were also studied.